Can We Flourish? - Christy Wenger (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
Teachers and students alike can agree on one shared truth of this past academic year: it was tough. Even though many of us found our way back into classrooms, sometimes masked and sometimes not, Covid continued to present new hurdles to our tried-and-true active teaching methods. Students struggled to keep up with the social and emotional demands of the face-to-face classroom after so many pandemic interruptions over the past two years, and teachers struggled to foster engagement and make meaningful learning gains in their classes. I met weekly with the instructors in my writing program to talk through classroom engagement and to brainstorm new ways to keep our students participating, learning, and simply just showing up for class. Just about every campuswide workshop I held through my Center for Teaching and Learning focused in some way on getting students engaged in class and involved in their learning. Inevitably, these pedagogical discussions of our classrooms gave way to connected conversations about the emotional state of those in attendance, faculty and staff who were not only carrying the burden of increased emotional labor through the pandemic as teachers but also as sisters, brothers, spouses, and more. The consensus was clear: no one on campus was flourishing.
Keywords: JAEPL